"The influence of orbital vector on involutional entropion and ectropion". (2nd January 2018) - Rajabi, Mohammad Taher; Gholipour, Farshad; Ramezani, Koosha; Hosseini, Seyedeh Simindokht; Rajabi, Mohammad Bagher; Tabatabaie, Seyed Ziaeddin
ABSTRACT: Purpose : This study aimed to evaluate the effect of orbital vector and other biometric parameters (i.e. axial globe length, axial globe projection) on the development of involutional entropion or ectropion. Methods : In this cross-sectional study, 167 eyes from 132 patients were included. Of these eyes, 128 had involutional entropion and 39 had involutional ectropion, all of lower lids. The axial globe projection was measured using Hertel exophthalmometry; axial globe length was assessed by A-mode ultrasound; and orbital vector was determined clinically. Patient-specific categorical variables and continuous variables were compared using the chi-square test and the two-sided t test, respectively. Correlations were derived using the Pearson correlation. Results : The percentage of females was 59% and 33.3% in the entropion group and in the ectropion group, respectively. A significant association was found between the gender and type of eyelid malposition ( p  = 0.015). Exophthalmometry reading was greater in the ectropion group than in the entropion group (17.7 ± 2.5 versus 10.8 ± 3.7 mm, respectively; p  < 0.001). There was no significant correlation between axial globe length and exophthalmometry reading. Positive orbital vectors were observed in 87.5% of eyelids with involutional entropion. Negative orbital vectors were observed in 92.3% of eyelids with involutional ectropion ( p  < 0.001). Patients with negative orbital vectors showed greater axial globe projection than patients with positive orbital vectors (18.0 ± 2.1 versus 10.6 ± 3.5 mm, respectively; p  < 0.001). Conclusions : There is an association between orbital vector measurement and involutional entropion and ectropion. Measuring the orbital vector may help predict the development of these lid malpositions.